Beating the Odds : Sustaining Inclusion in Mozambique's Growing Economy - Fox, Louise (Washington, DC : World Bank, 2012)
This assessment, reflecting poverty's many dimensions in Mozambique, combines multiple disciplines and diagnostic tools to explore poverty. It draws on a combination of approaches and tools from three separate analytical diagnostics developed by the World Bank: poverty assessment, country gender assessment, and country social analysis. It uses monetary, human, and social indicators and combines quantitative and qualitative approaches to understand trends in poverty and the dynamics that shape them. The objective is to support the development and implementation of pro-poor policies that really work by taking poverty's multiple dimensions into account. Because Mozambique has not collected nationally representative household survey data measuring poverty status and outcome indicators since 2003, the report focuses primarily on the changes in poverty and household community welfare through that year. When data are available after 2003, the assessment uses them, including data from a special non representative survey developed for this report-the poverty and vulnerability survey. The starting point for the analysis uses multiple quantitative and qualitative indicators that describe levels of and changes in opportunities and outcomes for households and communities in Mozambique since 1997. The rest of the report explains these changes.